Exploring termite-microbe symbiosis: Mechanisms, evolution and biotechnological potential - Mardani Abdul Halima; Clemente Michael Wong Vui Linga; Kamarul Zaman Zarkasi; Homathevi Rahman; Nur Athirah Abdullah; Abdul Hafiz Ab Majid; Zarina Amina; Nurul Akmar Hussin (Malaysian Society for Molecular Biology and Biotechnology, 2025)
The symbiotic relationship between termites and their gut microbes is one of nature's most fascinating mutualistic interactions. Termites, renowned for their ability to decompose lignocellulosic materials such as wood, rely heavily on their gut microbiota, which includes bacteria, archaea, and protozoa, each playing specific roles in breaking down cellulose, hemicellulose, and lignin. This complex partnership not only enables termites to thrive in low-nutrient environments but also supports nitrogen metabolism and provides essential nutrients for their survival. The termite gut is highly compartmentalized, creating various microenvironments that support diverse microbial communities and facilitate metabolic processes, including fermentation in anoxic conditions. Shaped by evolutionary pressures, this symbiotic relationship has resulted in specialized adaptations that optimize lignocellulose degradation and nitrogen cycling. This review explores the mechanisms of termite-microbe symbiosis, their functional roles across different taxa, the structural and functional compartmentalization of the termite gut, and the evolutionary dynamics driving this mutualistic relationship. In addition, this review highlights the ecological and biotechnological significance of termite-microbe symbiosis, offering valuable insights into efficient lignocellulose degradation and nutrient recycling mechanisms that could inspire future applications in sustainable bioenergy and waste management.